Makna rohani bagi remaja dan dewasa Kristen Protestan melalui photo elicitation - Evans Garey; Anita Novianty (Konsorsium Psikologi Ilmiah Nusantara, 2026)
The term rohani is used by individuals in Indonesia to refer to the human soul or spirit. However, scientific studies on the meaning of rohani remain limited, highlighting the need for a deeper understanding of this contextualized concept. This study involved Protestant Christian teenagers and adults (n = 26), with ages ranging from 15–68 years. A qualitative approach was employed using the photo elicitation method, and the data were analyzed through thematic analysis. The findings identified several primary themes of rohani meaning, including personal experiences, people-relationships, nature, religious activities, and places of worship. In addition, several emergent themes were identified, such as symbols, moral values, cues, and self-care. These findings suggest that the meaning of rohani not only reflects individuals’ efforts to seek the sacred or the divine, but also relates to an orientation toward personal well-being.